Characteristics of collecting folksong material at the intersection of peoples and cultures - Pisk, Marjeta (Traditiones (Ljubljana), 2005)
In the program of the Committee for the Collection of Slovenian Folk Song, the Princely County of Gorizia and Gradisca was poorly represented in the songs transcribed. The small number of transciptions was partly the results of inactivity on the part of committee member Ivan Kokošar, but even more so due to changes in how folk songs were valued in that region as the consequence of the activity of the choirs of the reading rooms and societies
Keywords: Kokošar, Ivan, 1860-1923; zbirateljstvo; slovenska ljudska glasba; slovenske ljudske pesmi; pevski zbori; Gorica; Gradišče; zgodovinski pregledi